The Role of Ferulic Acid in Selected Malignant Neoplasms - Anna Markowska; Janina Markowska; Joanna Stanisławiak-Rudowicz; Katarzyna Kozak; Otton Krzysztof Roubinek; Magdalena Jasińska (Molecules)
Ferulic acid (FA) is a polyphenol that is found in plants and fruits. It has a wide range of anticancer properties, including participating in cell apoptosis, inhibiting invasion and angiogenesis, and acting synergistically with standard cytostatic agents in malignant tumors. A range of molecular mechanisms are involved in anticancer activity and include the following ones: activation of cell-cycle-related proteins and enzymes such as p53, p21, Bax, and pro-caspases 3 and 9, reduction of cyclin D1 and E, proapoptotic Bcl-2, MMP-9, and NF-kV, which decrease VEGF, leading to cell cycle arrest at G0/G1 phase and death of cancer cells. Other mechanisms inhibit several pathways: PI3K/AKT/mTOR, Notch, and Wnt, which are associated with downregulation of proliferation, invasion, metastasis, and angiogenesis. FA can induce activation of ROS, leading to DNA damage in cancer cells. In vitro and in vivo studies have demonstrated the significant antitumor activity of FA in breast cancer, particularly when used in combination with cytostatic agents. In vitro studies on cervical cancer cell lines have reported similar anticancer activity of FA. This includes inhibition of cell proliferation and induction of apoptosis by downregulating antiapoptotic proteins. A case-control study conducted in Italy found that men with histologically confirmed prostate cancer had notably lower levels of FA compared to controls. Molecular in vitro studies have suggested that FA may have various effects on the signaling pathways linked to a reduction in the risk of prostate cancer, and it may act in synergy with δ-tocotrienol, which is a derivative of vitamin E. In vivo and in vitro studies on colorectal cancer have demonstrated the effects of FA on the early development of this cancer—inhibition of abnormal crypt foci (ACF-aberrant crypt foci), as well as the reduction in cancer cell viability and apoptosis through molecular changes, mainly a decrease in EGFR expression. The poor water solubility of FA makes it an attractive candidate for use as nanoparticles.